From plate to waste: a cross-sectional study of food waste trends in Al Ahsa, Saudi Arabia - Al Khatib, Alissar; Hassanein, Salwa; Abdrbo, Amany; Almari, Mohammed; AL-Turaiki, Sommanah M.; Alkhunaizi, May; Antar, Ahmad (Frontiers in Sustainable Food Systems, 2024)
Background: Food waste is a global concern that needs special attention and urgent actions to reduce the amount of wasted food. This study aims to investigate the trend of food waste in Al Ahsa; Methods: This is a cross-sectional study designed to analyze the factors associated with the generation of wasted food within Al Ahsa community. Results: The results showed that out of 257 participants, 82.9% were of Saudi nationality, 83.3% were females, 69.6% below 34 years and the family sizes mean was around 6. The majority of study participants were unemployed (62.3%), the employed ones were in healthcare field (56.4%). No significant gender differences was found in terms of other food waste-related variables. No significant association was found with age and occupation. Non-Saudi participants significantly report a lower frequency of wasting food and a higher rate of attitudes toward food waste sorting with p = 0.02 and p = 0.02 respectively. Working participants showed significant differences in terms of attitudes toward food waste sorting (p=.002), attitudes toward reducing food waste (p=.042), and the amount of food wasted per day (p=.010) when compared to those who are not working. Doctorate level of education exhibited significant (p=.002) attitudes toward food waste sorting and those who are in the commerce field of education had higher mean scores (M = 2.81, SD = 0.84) to reduce food waste. The cause of food waste was related to expiry date (61.1%). The common cause of wasting food when eating out or ordering online, was related to participants' preference for trying a variety of dishes (40.1%). The participants adherent to home-cooked food during pandemic (mean 3.85, SD 1.40). Males reported a slightly higher impact of COVID-19 on their dietary habits when compared to females (p = 0.04). The majority of participants agreed that sharing food with neighbors decreases food waste (Mean = 3.96, SD = 1.32). Moreover, they do not throw food due to religious and cultural beliefs (Mean = 3.36, SD = 1.60). Conclusion: Creating educational campaigns, promoting sustainable waste management and integrating technology to reduce food waste are recommended to achieve Saudi vision 2030.